Cases of contact lens related Acanthamoeba keratitis - Mohamed Kamel Abd Ghani,; Faridah Hanum Anuar,; Norazah Ahmad,; Norain Abdullah, (penerbit ukm, 2004)
Acanthamoeba keratitis is a potentially blinding ocular disease that is often misdiagnosed and remains difficult to treat. If not diagnosed early, it can be devastating to vision. Acanthamoeba keratitis may be associated with previous ocular trauma but the majority of cases in the developed world are associated to contact lens wear. We present two cases of contact lens related Acanthamoeba keratitis whose diagnosis were missed at initial presentation. The history, clinical findings and treatment instituted are briefly discussed here. In the light of prevention of the disease, lessons learnt from these cases especially on the role of poor hygienic practice during of contact lens wear in precipitating the disease, are highlighted.